Letter (copy) : Further medical unit for Spain - Tewson, Vincent
041-0139-001 Our Ref: HVT/FC/EK/120. 16th October, 1936. Dr. C. Brook, Spanish Medical Aid Committee, 24, New Oxford Street, London, W.C.1. Dear Dr. Brook, FURTHER MEDICAL UNIT FOR SPAIN. I desire to acknowledge receipt of your letter of the 14th instant in regard to the sending of a further Unit to Spain. I hope to have the opportunity early next week of bringing your letter forward for consideration and I will communicate with you again as soon as possible. Yours sincerely, for Joint Secretary. 292/946/41/139